LOCATION BASED SERVICE PADA PEMETAAN GEOGRAFIS MOBIL UNIT DONOR DARAH - Khofifah; Christanto, Febrian Wahyu (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
The Indonesian Red Cross (Palang Merah Indonesia or PMI) has established a special unit to meet blood donation needs, known as the Blood Donor Unit or UDD. The UDD of PMI in Semarang City has a Mobile Unit program involving blood donation activities that are carried out upon request from groups or institutions seeking collaboration with the UDD of PMI in Semarang City. Currently, to find information about the locations of blood donation activities organized by PMI in Semarang, donors can check through social media. However, the disseminated information only includes addresses, and donors do not know which location is closest to them. Moreover, groups or institutions that have not established collaboration with PMI, when requesting blood donation activities, must come to PMI in Semarang City. To address this issue, the Geographic Mapping Application for the Blood Donor Mobile Unit is deemed necessary as a navigation information tool for blood donation locations around the city of Semarang. Developed using the prototype system development method and built using LeafletJS, a JavaScript library useful for constructing interactive web-based maps with the Location Based Service (LBS) method, this system functions to manage mobile unit activities and find the nearest mobile unit location for potential blood donors. The system achieves a test result satisfaction rate of 92% for users. It is expected that this system can be accessed by the entire community and be accepted by the UDD of PMI in Semarang City as a navigation tool for potential blood donors.